The gut virome in health and disease: new insights and associations. Issue 6 (9th November 2022) - Shareefdeen, Hiba; Hill, Colin
Abstract : Purpose of review: Recent years have seen great strides made in the field of viral metagenomics. Many studies have reported alterations in the virome in different disease states. The vast majority of the human intestinal virome consists of bacteriophages, viruses that infect bacteria. The dynamic relationship between gut bacterial populations and bacteriophages is influenced by environmental factors that also impact host health and disease. In this review, we focus on studies highlighting the dynamics of the gut virome and fluctuations associated with disease states. Recent findings: Novel correlations have been identified between the human gut virome and diseases such as obesity, necrotizing enterocolitis and severe acute respiratory syndrome coronavirus 2 infection. Further associations between the virome and cognition, diet and geography highlight the complexity of factors that can influence the dynamic relationship between gut bacteria, bacteriophages and health. Summary: Here, we highlight some novel associations between the virome and health that will be the foundation for future studies in this field. The future development of microbiome-based interventions, identification of biomarkers, and novel therapeutics will require a thorough understanding of the gut virome and its dynamics.